Acts of alienations and transactions in the institutes of consecrated life and associations of apostolic life - KALETA, PAWEŁ (Prawo Kanoniczne, 2019)
The points explored in this study refer to the guidelines published by the Congregation for Institutes of Consecrated Life and Societies of Apostolic Life entitled Economy at the service of the charism and mission. These guidelines aim to provide guidance to administrators involved in the practical implementation of acts of alienation and transactions. All sales exceeding the maximum amount pursuant to can. 638 § 3 require the Congregation’s authorization, regardless of whether the goods are ascribed to the stable patrimony. In Poland for instance, the maximum amount is €1.000.000. Superior general should present such requests for authorization, having initially sought consent from their council. Apart from the requirement contained in the 1983 Code of Canon Law, the Congregation also requires the submission of a sworn assessment of the goods to be alienated. The alienation of goods is not an independent act. The Congregation emphasizes that major superiors should „act together” with the local church. Prior to submitting a request for authorization, he or she should therefore request the written opinion of the ordinary of the place where the property is located. Those major superiors intending to proceed with the closure of a community or work, should also inform other religious institutes in the same area about their intentions. This should be done in order to ensure that the diocese does not become deprived of religious congregations. In order to reduce risks arising from alienation or transactions, the Congregation recommends collaboration with external professionals (lay people or members of other religious institutes) in order to avoid the rash recourse of engaging a single professional worker. If possible, the Congregation recommends that priority is given to church institutions to purchase these alienated goods.